2023
DOI: 10.1021/acsestwater.2c00460
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Recovery Methods for Wastewater Surveillance of Arthropod-Borne and Enveloped Viruses

Abstract: The potential public health utility of arthropod-borne virus (arbovirus) wastewater surveillance (WWS) warrants the effort of establishing an effective sample preparation workflow. Here, we investigated different sample clarification, concentration, and extraction methods to determine the best workflow for recovery of spiked arboviral and murine hepatitis virus RNA signals in wastewater. We determined that the sample clarification method with the least loss is filtration through a 0.22 μm filter (9.06 ± 3.68%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Campus residential samples were processed by ultrafiltration using protein concentrators excluding a three-week period from 11 October to 2 November 2021 where the PEG method of viral particle concentration was used due to a global supply chain shortage of concentrators. Efficiencies of both methods for recovering SARS-CoV-2 were comparable (not statistically different) during internal evaluation (unpublished data; Chandra et al, 2023). Wastewater samples were first centrifuged at 4000g at 4 °C for 30 min to remove large debris.…”
Section: Sample Concentration and Rna Extractionmentioning
confidence: 90%
“…Campus residential samples were processed by ultrafiltration using protein concentrators excluding a three-week period from 11 October to 2 November 2021 where the PEG method of viral particle concentration was used due to a global supply chain shortage of concentrators. Efficiencies of both methods for recovering SARS-CoV-2 were comparable (not statistically different) during internal evaluation (unpublished data; Chandra et al, 2023). Wastewater samples were first centrifuged at 4000g at 4 °C for 30 min to remove large debris.…”
Section: Sample Concentration and Rna Extractionmentioning
confidence: 90%
“…Serotyping is based on PCR-confirmation. State-and county-aggregated incident case data were digitized from the weekly reports for the study period (18 June 2023 -30 September 2023; MMWR weeks [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Data on the specific DENV serotype responsible for each incident case are available for only state-aggregated, travel-associated cases, and county-aggregated locally-acquired cases.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 Laboratory spike-in experiments have demonstrated that DENV can persist in wastewaters for days to weeks. 2729…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wastewater monitoring has been previously proposed as a promising tool for population-level monitoring of DENV, but limited studies testing natural wastewater have not detected the virus. , DENV is an enveloped virus in the Flaviviridae family with a single stranded RNA genome, and is shed in the urine and saliva of infected individuals and thus likely to be excreted into wastewater. Quantitative data are limited, but shedding in urine has been estimated to be up to around 10 3 RNA copies/mL (or 10 6 RNA copies per day) at the peak of shedding, approximately 8–10 days after symptom onset. , Peak shedding occurs during days 0–7 in saliva. DENV shedding in human stool is currently unknown; however, Zika virus, another mosquito-borne virus of the same genus as DENV, has been detected in rectal swabs of infected humans, suggesting DENV might be shed in human stool as well. , Laboratory spike-in experiments have demonstrated that DENV can persist in wastewaters for days to weeks. …”
Section: Introductionmentioning
confidence: 99%